Altered spontaneous brain activity patterns in strabismus with amblyopia patients using amplitude of low-frequency fluctuation: a resting-state fMRI study - Min, You-Lan (Neuropsychiatr Dis Treat, 2018)
OBJECTIVE: Previous studies have demonstrated that strabismus or amblyopia can result in markedly brain function and anatomical alterations. However, the differences in spontaneous brain activities of strabismus with amblyopia (SA) patients still remain unclear. This current study intended to use the amplitude of low-frequency fluctuation (ALFF) technique to investigate the intrinsic brain activity changes in SA subjects. PATIENTS AND METHODS: A total of 16 patients with SA (6 males and 10 females) and 16 healthy controls (HCs; 6 males and 10 females) similarly matched in age, gender, and education status were recruited and examined with the resting-state functional MRI. The spontaneous brain activity changes were investigated using the ALFF technique. The receiver operating characteristic curve was performed to classify the mean ALFF signal values of the SA patients from HCs. The correlations between the ALFF values of distinct brain regions and the clinical manifestations in SA patients were evaluated in terms of the Pearson’s correlation analysis. RESULTS: Compared with HCs, SA patients had significantly decreased ALFF in the left cerebellum posterior lobe, left middle frontal gyrus, and bilateral thalamus. In contrast, SA patients showed increased ALFF values in the right superior frontal gyrus, right precuneus, left cuneus, and bilateral precentral gyrus. Nonetheless, there was no linear correlation between the mean ALFF values in brain regions and clinical features. CONCLUSION: Diverse brain regions including vision-related and motion-related areas exhibited aberrant intrinsic brain activity patterns, which imply the neuropathologic mechanisms of oculomotor disorder and vision deficit in the SA patients.